2013
DOI: 10.5295/cdg.110282jg
|View full text |Cite
|
Sign up to set email alerts
|

Trust as a consequence of perceived commitment: Implications on learning and innovation

Abstract: In this paper we try to achieve a double objective. On one hand, we try to figure out how employee's affective commitment perceived by the manager influence on her/his level of trust and also on the organizational learning capability (OLC). In addition, we analyze how manager trust influences on OLC. On the other hand, we study how these variables (affective commitment of employees, manager trust and OLC) determine product innovation. Applying structural equation model (Partial Least Squares -PLS-) on a sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 73 publications
0
4
0
2
Order By: Relevance
“…In the studies we conducted, we found trust is related to (NELSON, QUICK, 2003), communication (BECERRA, GUPTA, 2003;PORUMBESCU, PARK, OOMSELS, 2013), control mechanisms (DAS, TENG, 1998;KHODYAKOV, 2007;REED, 2001), risk (EARL, 2010;LIU, WANG, 2013) and creativity and innovation (BARSH, CAPOZI, DAVIDSON, 2008;GARCÍA-CRUZ;REAL, 2013;KOHTAMÄKj;KEKÄLE, VIITALA, 2004). Baird and St. Amand (1995) and Sako (1998) state that trust leads to increased productivity, reduced absenteeism and turnover, and promotes a favorable environment to creativity and innovation.…”
Section: Trustmentioning
confidence: 95%
“…In the studies we conducted, we found trust is related to (NELSON, QUICK, 2003), communication (BECERRA, GUPTA, 2003;PORUMBESCU, PARK, OOMSELS, 2013), control mechanisms (DAS, TENG, 1998;KHODYAKOV, 2007;REED, 2001), risk (EARL, 2010;LIU, WANG, 2013) and creativity and innovation (BARSH, CAPOZI, DAVIDSON, 2008;GARCÍA-CRUZ;REAL, 2013;KOHTAMÄKj;KEKÄLE, VIITALA, 2004). Baird and St. Amand (1995) and Sako (1998) state that trust leads to increased productivity, reduced absenteeism and turnover, and promotes a favorable environment to creativity and innovation.…”
Section: Trustmentioning
confidence: 95%
“…11 Enero -Junio 2017 RICEA El establecimiento de mecanismos para compartir el conocimiento en la organización no es una tarea sencilla. Debido a su naturaleza personal, es difícil definir, expresar, transmitir y compartir, por lo que el aprendizaje en la organización permite la adquisición y creación de conocimiento así como su generación y diseminación (Jiménez y Sánz, 2006;García y Real, 2013).…”
Section: Issn: 2007 -9907unclassified
“…El conocimiento es útil para generar nuevas ideas, sin embargo, el aprendizaje es el conducto para definir, transmitir y compartir el conocimiento dentro de la organización (Jiménez y Sánz, 2006;García y Real, 2013).…”
Section: Issn: 2007 -9907unclassified
“…Furthermore, trust is conceived as a necessary element of cohesion that provides consistency to social structures (García and Real, 2013), evidencing its importance for interpersonal relationships in a work team and impacting directly on the performance of an organization. Nevertheless, the trust a manager demonstrates towards his employees is perceived by the latter as a sign of organizational support, thereby impacting on the need to become involved in the development of a learning culture (García and Real, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The positive relationship between Commitment and Trust (Guinalíu and Jordan, 2016), and between Commitment and Organizational Commitment to Learning (García and Real, 2013), allow us to consider that cultivating the trust of employees in the company is a determining factor to impact performance positively. Guinalíu and Jordán (2016), in their research on building trust in virtual work teams, validate the hypotheses that link empathy, justice and leadership style with trusting the leader.…”
Section: Introductionmentioning
confidence: 99%